Assessment of Association of Asthma and Vitamin D - Mohanan C Manjakara; Vinod Babu (Asian Journal of Medical Research, 2019)
Background: The aim is to assess association of asthma and vitamin D. Subjects and Methods: Seventy- two patients in age ranged 1- 18 years of either gender with asthma were taken in this study. They were classified into 2 groups. Group I patients were treated with budesonide therapy and group II patients were treated with atomization inhalation of budesonide combined with salbutamol and Vit D supplementation. Healthy subjects were also enrolled. The levels of serum Vit D were determined by ELISA. Results: There were 20 males and 16 females in group I and 21 males and 15 females in group II. The mean weight was 17.4 kg in group I and 18.5 kg in group II, history of allergies was seen in 21 in group I and 24 in group II, eosinophil count in peripheral blood was 0.48 in group I and 0.44 in group II and childhood asthma control test score (C-ACT) was 16.7 in group I and 16.5 in group II. The mean vitamin D level in children with asthma was 17.5 ng/ml and in normal children was 32.6. The mean IgE level in children with asthma was 386.2 IU/ml and in normal children was 284.2 IU/ml. It was observed that Vit D levels were positively correlated with MEF25 and MEF50 not significantly correlated with FEV1, FVC, FEV1/FVC. Vit D levels were negatively correlated with IgE and were statistically significant at P<0.05. Conclusion: The serum Vit D levels of children with asthma were closely related to the acute asthmatic attacks.